EFFECT OF FRESH PILCHARDS ON PRODUCTION PERFORMANCE IN RAINBOW TROUT (Oncorhynchus mykiss Walbaum) NUTRITION - N. Plavša; V. Stanaćev; N. Milošević; D. Ljubojević; N. Puvača; J. Markov; M. Ćirković (Journal of Animal and Plant Sciences, 2012)
The study was to present the results of growing production of trout, which were conducted in full system pond with the surface of 4,164 ha, which is supplied with water of high quality, constant temperature 10 °C throughout the whole year. For the experiment we have used rainbow trout fry of an average weight of 88-90 g and length 190-210 mm. The experiment involved a total of 5240 individuals, which lasted 90 days. Nutrition of control groups was performed by standard industrial pellets, which contained 41.49% protein and 9.27% fat. Feeding the experimental group was performed with 75% standard industrial pellets and 25% of the meal is made fresh anchovies. This meal contained 36.49% protein and 8.89% fat. After 90 days we have achieved the following results: the experimental group achieved a total weight gain of 67.80 g (0.753 g/day), while the control group achieved total realized gain of 44.47 g( 0.494 g/day). The total increase in length of fish in the experimental group was 41.19 mm (0.457 mm/day), while the fish in the control group achieved a total increase of 29.410 mm. Feeding coefficient expressed on dry matter (kg DM) after 90 days in the control group was 1.92, while in the experimental group was 1.16. The fresh anchovies  in the amount of 25% of a meal gave gut results in the control group: increased weight gain of 47.94%, increased length growth of fish for 40.18% and reduced feed conversion 28.64% .
Keywords: rainbow trout; anchovy; production results; profitability.